2020
DOI: 10.1002/qua.26251
|View full text |Cite
|
Sign up to set email alerts
|

The π‐hole tetrel bond betweenX2TOandCO2: Substituent effects and its potential adsorptivity forCO2

Abstract: Quantum chemical calculations are applied to study the complexes between X2TO (X = H, F, Cl, Br, CH3; T = C, Si, Ge, Sn) and CO2. The carbon atom of CO2 as a Lewis acid participates in the C···O carbon bond, whereas its oxygen atom as a base engages in the O···T tetrel bond with X2TO. Most of complexes are stabilized by a combination of both C···O and O···T interactions. The interaction energy increases in the T = C < Ge < Sn < Si sequence for most complexes. Both the electron‐withdrawing halogen group and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 79 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…These electronic and geometrical parameters have been reported to correlate with the anion/CO 2 bond strength. 38,39 The amount of charge transferred from the anion to CO 2 strongly depends on the nature of the atom bonding to the carbon atom. As a general trend, the amount of charge transfer occurs in the following order: P > S N > O, reflecting the reverse of the atomic electronegativity.…”
Section: Hosted Filementioning
confidence: 99%
“…These electronic and geometrical parameters have been reported to correlate with the anion/CO 2 bond strength. 38,39 The amount of charge transferred from the anion to CO 2 strongly depends on the nature of the atom bonding to the carbon atom. As a general trend, the amount of charge transfer occurs in the following order: P > S N > O, reflecting the reverse of the atomic electronegativity.…”
Section: Hosted Filementioning
confidence: 99%
“…It is not uncommon for positive potentials to occur directly above planar molecules. 44–58 For example, the F substituents on hexafluorobenzene extract density from the carbon ring which leaves the area above this ring with a positive potential. Likewise for a simpler molecule such as F 2 CO where the positive region is situated above the C. These positive areas above planar molecules are commonly designated as π-holes, and like their σ-hole cousins, can engage in strong noncovalent bonding with a nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al studied the π-hole TBs formed by X 2 TO (X = H, F, Cl, Br, CH 3 ; T = C, Si, Ge, Sn) and CO 2 and found that the interaction energy can be as high as 51 kJ mol −1 . 30 Chandra et al identified a C⋯N π-hole TB between CO 2 and NH 3 by means of infrared spectroscopy and quantum chemical methods. 31…”
Section: Introductionmentioning
confidence: 99%